Pengaruh Keterlibatan Kerja Terhadap Kinerja Dengan Dimediasi Oleh Komitmen Organisasional Pada Karyawan Pt. Sekar Laut Di Surabaya - Wijaya, Sean (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
To be able to survive and develop in the competitive environment, a company must be able to keep and increase the performance. There are two variables that relate to the performance: organizational commitment and job involvement. Organizational commitment is stated that has the ability to effect the mediation of job involvement toward performance. The aim of this research is to determine the relationship between job involvement, performance, and organizational commitment within an organization. This research is a descriptive study that describes the relationship between the variables studied to determine the relationship between job involvement, and performance to be mediated by organizational commitment. The subject of this research is PT. Sekar Laut in Surabaya. Variables of this research includes: Independent Variable which is job involvement, Mediation Variable which is organizational commitment, and Dependent Variable which is Job Performance. The total amounts of these samples are 98 samples. The data analysis technique that was used is hierarchical regression. The finding of this research is that job involvement has a significant affect to organizational commitment. Organizational commitment has impacted positively the job performance of PT. Sekar Laut’s employees. Organizational commitment is able to the mediate the effect of job involvement toward job performance. However, job involvement only have partial mediating effect on the relationship between organizational commitment and job performance.